A study of inter-individual variability in the Phase II metabolism of xenobiotics in human skin. (August 2018) - Spriggs, Sandrine; Cubberley, Richard; Loadman, Paul; Sheffield, David; Wierzbicki, Antonia
Highlights: Evaluated various handling and storage conditions post-surgery. Developed method for preparation of S9 with emphasis on cofactor addition. Activity of Phase II enzymes measured in up to 90 individuals. Comprehensive statistical analysis of results. Abstract: Understanding skin metabolism is key to improve in vitro to in vivo extrapolations used to inform risk assessments of topically applied products. However, published literature is scarce and usually covers a limited and non-representative number of donors. We developed a protocol to handle and store ex vivo skin samples post-surgery and prepare skin S9 fractions to measure the metabolic activity of Phase II enzymes. Preincubation of an excess of cofactors at 37 °C for fifteen minutes in the S9 before introduction of the testing probe, greatly increased the stability of the enzymes. Using this standardised assay, the rates of sulphation (SULT) and glucuronidation (UGT) of 7-hydroxycoumarin, methylation (COMT) of dopamine and N-acetylation (NAT) of procainamide were measured in the ng/mg protein/h (converted to ng/cm 2 /h) range in eighty-seven individuals. Glutathione conjugation (GST) of 1-chloro-2, 4-dinitrobenzene was assessed in a smaller pool of fifty donors; the metabolic rate was much faster and measured over six minutes using a different methodology to express rates in μg/mg protein/min (converted to μg/cm 2 /min). A comprehensive statistical analysis of these results was carried out, separating donors by age, gender and metabolic rate measured.